Thought Insertion as a Self-Disturbance: An Integration of Predictive Coding and Phenomenological Approaches - Sterzer, Philipp; Mishara, Aaron L.; Voss, Martin; Heinz, Andreas (Frontiers in Human Neuroscience, 2016)
Current theories in the framework of hierarchical predictive coding propose that positive symptoms of schizophrenia, such as delusions and hallucinations, arise from an alteration in Bayesian inference, the term inference referring to a process by which learned predictions are used to infer probable causes of sensory data. However, for one particularly striking and frequent symptom of schizophrenia, thought insertion, no plausible account has been proposed in terms of the predictive-coding framework. Here we propose that thought insertion is due to an altered experience of thoughts as coming from “nowhere”, as is already indicated by the early 20th century phenomenological accounts by the early Heidelberg School of psychiatry. These accounts identified thought insertion as one of the self-disturbances (from German: “Ichstörungen”) of schizophrenia and used mescaline as a model-psychosis in healthy individuals to explore the possible mechanisms. The early Heidelberg School (Gruhle, Mayer-Gross, Beringer) first named and defined the self-disturbances, and proposed that thought insertion involves a disruption of the inner connectedness of thoughts and experiences, and a “becoming sensory” of those thoughts experienced as inserted. This account offers a novel way to integrate the phenomenology of thought insertion with the predictive coding framework. We argue that the altered experience of thoughts may be caused by a reduced precision of context-dependent predictions, relative to sensory precision. According to the principles of Bayesian inference, this reduced precision leads to increased prediction-error signals evoked by the neural activity that encodes thoughts. Thus, in analogy with the prediction-error related aberrant salience of external events that has been proposed previously, “internal” events such as thoughts (including volitions, emotions and memories) can also be associated with increased prediction-error signaling and are thus imbued with aberrant salience. We suggest that the individual’s attempt to explain the aberrant salience of thoughts results in their interpretation as being inserted by an alien agent, similarly to the emergence of delusions in response to the aberrant salience of sensory stimuli.